2009
DOI: 10.1016/j.ijsu.2009.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Varicocelectomy in men with nonobstructive azoospermia: Is it beneficial?

Abstract: High ligation varicocelectomy may offer nonobstructive azoospermic men an opportunity to have motile sperm via ejaculate and even the chance of natural conception, instead of the more bothersome assisted reproductive techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 20 publications
3
36
0
Order By: Relevance
“…However, the degree to which varicocele repair improves pregnancy rates and the success of assisted reproductive technology remains controversial. Varicoceles are associated with infertility but the significance of this relationship is uncertain; surgical or radiological repair of varicoceles is not recognized as appropriate treatment for infertility [20,[26][27][28][29] . Scrotal US is used to examine the testes in at least two planes, the transverse and longitudinal; the size is measured and the echotexture is evaluated [30] .…”
Section: Scrotal Us Findings In Non Obstructive Azoospermiamentioning
confidence: 99%
“…However, the degree to which varicocele repair improves pregnancy rates and the success of assisted reproductive technology remains controversial. Varicoceles are associated with infertility but the significance of this relationship is uncertain; surgical or radiological repair of varicoceles is not recognized as appropriate treatment for infertility [20,[26][27][28][29] . Scrotal US is used to examine the testes in at least two planes, the transverse and longitudinal; the size is measured and the echotexture is evaluated [30] .…”
Section: Scrotal Us Findings In Non Obstructive Azoospermiamentioning
confidence: 99%
“…One study was excluded due to duplication of data in a later paper [7,8]. Another study was excluded because final analysis of outcome detected a subject diagnosed with cryptozoospermia [2]. Altogether 12 studies were included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…Varicocele often results in sperm production disorders marked by the abnormal quality of semen, ranging from oligospermia to azoospermia [2]. Non-obstructive azoospermia was reported at 4.3 to 13.3% in infertile men with clinical varicocele [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data analyzed in the current study revealed that 538 participants from diverse area in the world, issue from 7 original sources underwent varicocelectomy following by ARTs during the period of 2001-2011; this may be sufficient to assess male infertility due to varicoceles regarding the existing controversies [4,7,14,16,24,25] and based on updated recommendations and guidelines for good practices [3,4,[19][20][21]23]. The mean age of 4 studies showed mid advanced age (34 years old) for men to conceive; most studies suggested the average interval of about 6 months from varicocelectomy to ART [1,24,26,27].…”
Section: Discussionmentioning
confidence: 97%